If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 38 = 12x Reorder the terms: 38 + 5x = 12x Solving 38 + 5x = 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 38 + 5x + -12x = 12x + -12x Combine like terms: 5x + -12x = -7x 38 + -7x = 12x + -12x Combine like terms: 12x + -12x = 0 38 + -7x = 0 Add '-38' to each side of the equation. 38 + -38 + -7x = 0 + -38 Combine like terms: 38 + -38 = 0 0 + -7x = 0 + -38 -7x = 0 + -38 Combine like terms: 0 + -38 = -38 -7x = -38 Divide each side by '-7'. x = 5.428571429 Simplifying x = 5.428571429
| 9+10=21*1 | | 4=-2x-25 | | 6+0.5x=42 | | 3a+8=26 | | 4(q+3)+2q=-12 | | 6a+4b+4a+5a= | | 10x-2-6x=3x+2+x | | 7*0.15+0.15s=5.55 | | 2F-7.9-F+1.5=-3.2-1.7 | | 8m-9n-2n=6n | | -8=2(3-2n) | | 11x+12=5x+60 | | 3(y-3)=2y+9+y | | -5E-32+6E=19 | | -2(4+x)=25 | | 3.29-0.14x=5x-3.135 | | x^3+x^2+36*x-23=0 | | 7x+2y+(-8x)-3y= | | 40+s=61 | | 11=c-2 | | 4(x-1)-(3x+2)=2(x+7) | | 54x^2+40x=0 | | -1.80=4.0x-4.9(x^2) | | 5x-12=6x-16 | | -10-m=6m-10 | | x^3-19683=0 | | 9x-2(x-7)=2(x-2)+1 | | 5p=2p-4qforp | | -1.80=4.9x-4.9(x^2) | | -4=-5+x | | -2m+(-6m)= | | 10x-1=9x+8 |